Analysis of Geotextile Reinforced Road Embankment Using PLAXIS 2D. (2015) - Wulandari, Paravita Sri; Tjandra, Daniel
Abstract: Geotextiles have been increasingly applied as reinforcement in road embankments on soft soil. The purpose of this study is to determine the optimum tensile strength of geotextile as the reinforcement in road embankment considering the allowable factor of safety and displacement. The stability analysis of the road embankment has been done by finite element method using PLAXIS 2D. In this study, three types of sequence modeling were conducted. First, the stability of road embankment without any reinforcement was analyzed. Second modeling was to determine the length of geotextile reinforcement considering the stability of the model road embankment. The last sequence was to investigate the stability of the model reinforced embankment with various tensile strength of geotextiles reinforcement. The result of this study showed that the optimum tensile strength of geotextiles was strongly influenced by the factor of safety.